Using Mobile Technology to Reduce Engagement in Stereotypy: A Validation of Decision-Making Algorithms. Issue 2 (March 2019) - Préfontaine, Isabelle; Lanovaz, Marc J.; McDuff, Emeline; McHugh, Catherine; Cook, Jennifer L.
We developed an iOS app, the iSTIM, designed to support parents of children with autism spectrum disorders (ASD) in reducing common repetitive vocal and motor behavior (i.e., stereotypy). The purpose of our study was to preliminarily test the decision-making algorithms of the iSTIM using trained university students to implement the assessments and interventions. Specifically, we examined the effects of the iSTIM on stereotypy and functional engagement in 11 children with ASD within alternating treatment designs. Using the iSTIM reduced engagement in stereotypy for eight participants and increased functional engagement for four of those participants. Our results indicate that the iSTIM may decrease engagement in stereotypy but that some of the decision-making algorithms may benefit from modifications prior to testing with parents.